2018
DOI: 10.1002/ange.201803058
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on the Actinic Step of Donor–Acceptor Stenhouse Adduct Photoswitching

Abstract: Donor–acceptor Stenhouse adducts (DASAs) are negative photochromes that switch with visible light and are highly promising for applications ranging from smart materials to biological systems. However, the strong solvent dependence of the photoswitching kinetics limits their application. The nature of the photoswitching mechanism in different solvents is key for addressing the solvatochromism of DASAs, but as yet has remained elusive. Here, we employ spectroscopic analyses and TD‐DFT calculations to reveal chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
3
11
0
1
Order By: Relevance
“…Interestingly, after adding water into a toluene solution of linear DASA-N (toluene:water = 6:1, v/v), we found that the linear DASA-N spontaneously converts to cyclic DASA-N, even without light, this is in good accordance to the previous reports ( Fig. 2b) 1,2,[18][19][20] . The process is extremely slow compared with the light-induced isomerization, and onlỹ 30% of cyclic DASA-N can be obtained after 10 h, and the process is finished in 40 h ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Interestingly, after adding water into a toluene solution of linear DASA-N (toluene:water = 6:1, v/v), we found that the linear DASA-N spontaneously converts to cyclic DASA-N, even without light, this is in good accordance to the previous reports ( Fig. 2b) 1,2,[18][19][20] . The process is extremely slow compared with the light-induced isomerization, and onlỹ 30% of cyclic DASA-N can be obtained after 10 h, and the process is finished in 40 h ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…Since the earliest report cyclic DASAs have been found to be more stable when water exists 1 . The linear-to-cyclic isomerization occurs under dark in aqueous environment was also noticed by Feringa's group earlier in 2016 and 2018 [18][19][20] . However, to our knowledge no research is focusing on the mechanism of the water-induced isomerization and the relationships between DASAs and H 2 O molecules, which are important for the understanding, development and application of DASAs.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…(2) The excited state transfers to intermediate Aˈ through a C2‐C3 isomerization in nanoseconds as an actinic step, which has been observed by evolution‐associated difference spectra (EADS); [ 61‐63 ]…”
Section: Photoswitching Of Sps and Dasasmentioning
confidence: 99%